Pollen resource and seasonal cycle of Thygater aethiops (Hymenoptera: Apidae) in an urban environment (Bogotá-Colombia) - Pinilla-Gallego, Mario Simon (2016)
Thygater aethiops is a native bee that can be found in parks and gardens in diverse urban areas such as those in the city of Bogotá (Colombia). However, little is known about its biology as well as ecological adaptations to urban areas. This study aimed to describe the seasonal cycle and daily foraging activities of T. aethiops, as well as identify the pollen resources used by this bee over a year in a population nesting in an aggregation in the “Parque Nacional Enrique Olaya Herrera” in Bogotá. Changes in the nest activity were monitored weekly by counting the number of active nests in the aggregation between December/2012 and February/2014. To determine the daily foraging activity, the numbers of bees entering their nests over a period of 10 minutes every hour between 8:00 and 14:00 h were recorded. Females with pollen loads entering to their nest were captured weekly, between September/2012 and August/2013, and their pollen loads analyzed. Three nesting peaks occurred after the precipitation peaks, but the number of active nests was not correlated with precipitation. The nesting activities stopped in a large number of the active nests (20-50 % of nests) after an anthropic disturbance was registered in the nesting area. Bees forage for nectar and pollen between 8:00 and 14:00 h, with a peak at 10:00 h. Daily foraging activity changed during the study period due to anthropic disturbance. There was not a significant relationship between air temperature and the number of females entering their nests. Foraging activities did not change between the dry and rainy seasons. A total of 26 pollen types were found in 169 pollen loads. Ulex europaeus (Fabaceae) and Solanum laxum (Solanaceae) were the most abundant plants represented on the pollen load across the study period. According to these results, T. aethiops would be considered a mesolectic species. The ability of T. aethiops to use different pollen resources both native and exotic, as well as to presumably recover its population after disturbances, are characteristics that may have allowed this bee to adapt to urban environments. Knowledge on the floral resources as well as other biological features of this bee species is important to promote its conservation in urban areas.